lan Gibson, Federico García Lorca, t. 1: De Fuente Vaqueros a Nueva York, 1898-1929. Grijalbo, Barcelona, 1985; 721 pp. - Cifuentes, Luis Fernando (Nueva Revista de Filología Hispánica (NRFH), 1985)
Se reseñó el libro: Federico García Lorca, t. 1: De Fuente Vaqueros a Nueva York, 1898-1929.